Menciptakan Lingkungan Bersih Bebas dari Demam Berdarah Dengue - Arifin, Syamsul; Rahmat, Besuki; Darim, Abu; Nuryadi, Nuryadi; Rosita Dewi, Anna; Setowati, Nunik; Ismail, Mahmud (PPPM Stikes Banyuwangi, 2023)
Background: Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus infection. Dengue fever is transmitted by the Aedes aegypti and Aedes albopictus mosquitoes. Based on data in Madiun Regency in 2019 there were 305 sufferers and 4 people died from DHF. The purpose of carrying out community service activities (PKM) and Community Service Lectures (KKN) in Mojorayung Village, Wungu District, Madiun Regency is to provide awareness of healthy living and play an active role in preventing DHF. The method of this PKM is using an approach to the community through socialization and education on prevention of DHF. The community is also invited to play an active role in maintaining cleanliness so that they are not susceptible to dengue. The result of this PKM, the people of Mojorayung Village have begun to experience an increase in living a clean and healthy life. The community also began to actively carry out community service in environmental cleaning activities. Discussion of the PKM activities carried out by students together with STIE Pemuda lecturers, besides being able to help with problems that occur in Mojorayung Village regarding prevention of DHF, can also increase public awareness of the importance of living a clean and healthy life.